SOSIALISME DALAM UTOPIA SUBAK: PERGESERAN DAN KRISIS NILAI KOLEKTIVITAS DI ERA BALI MODERN - Destishinta, Lucia Yerinta; Priadiantoro, Budhi Cahyo (UI Scholars Hub, 2025)
As a system of irrigation and traditional organization in Bali, Subak has functioned for centuries in collectively managing the equitable distribution of water resources. Its role as a socio-ecological institution is based on local values; it reflects the principles of collectivity and mutual cooperation, which align with the idea of socialism. However, agricultural modernization and the expansion of agrarian capitalism have caused a shift in collective work patterns within the Subak system. Based on this phenomenon, this article aims to examine these changes from a socialist perspective and their implications for the sustainability of the agricultural system in Bali. Using qualitative, literature-based methods, this study examines the socio-economic dynamics that influence Subak and the efforts of the Subak community to maintain this system amidst changing times. This study concludes with the finding that although the principle of collectivity within Subak still persists, market economic intervention has weakened the solidarity and independence of the Subak community.